A Assembleia de Deus e a política no Estado de Goiás (1980-2010) - Lopes, Lindiogenes Ferreira (2016)
This provision tralhado, as an object of religious studies with emphasis in Sociology, aims to present the church the Assemblies of God and their insertion aspects of party politics in the state of Goiás, with historical period from 1980 to 2010. For that, had the significant contribution of the theoretical apparatus of domination of Max Weber and the symbolic power Pierre Bourdieu, proposing as these joints are established in the religious landscape, especially with regard to political and religious activities. Continuing the text is split into three main moments of the research proposes the history of the Pentecostal movement and consequently how this phenomenon gaining strength in Brazil to achieve performance space in the political arena. Continuing the research object enters the picture, tracing the historical data of the Assemblies of God in Brazil and in the State of Goiás, as well as its forms and administrative strategies. The analysis continues in the third moment is specifically presented to party politics in the ADs, prioritizing the action of leadership related church policy goiano ground, prioritizing the three decades drawn the theme, from the first moment of access ADs in policy, through changing assembleiano pentecostal behavior on such practices to the final conquest of the political field. The aim of this study was to understand how the Assembly of God church, directed by its influential leaders, migrates from anonymity to the political leadership, it is therefore decisive in any elections.